Methane Adsorption on Shale: Insights from Experiments and a Simplified Local Density Model - Luo Zuo; Yupu Wang; Wei Guo; Wei Xiong; Shusheng Gao; Zhiming Hu; Shen Rui (Adsorption Science & Technology)
We herein present a method for predicting adsorption isotherms of methane on shale using the simplified local density (SLD) theory: First, the adsorption isotherms of methane on shale samples were measured and then its adsorption on illite, illite/smectite mixed layer, chlorite, type I, type II and type III kerogen was described with the SLD theory. Second, based on the SLD parameters obtained from adsorption data on kerogen, clay minerals and the composition of the studied shale, we predicted adsorption capacity of the shale using a linear combination of the adsorption capacities of the pure substances weighted by their relative abundance.